Comparative transcriptome and metabolome analyses of cherry leaves spot disease caused by Alternaria alternata - Pan, Liu-Yi; Zhou, Jing; Sun, Yan; Qiao, Bai-Xue; Wan, Tian; Guo, Rui-Quan; Zhang, Juan; Shan, Dong-Qian; Cai, Yu-Liang (Frontiers in Plant Science, 2023)
Alternaria alternata is a necrotrophic fungal pathogen with a broad host range that causes widespread and devastating disease in sweet cherry (Prunus avium). We selected a resistant cultivar (RC) and a susceptible cultivar (SC) of cherry and used a combined physiological, transcriptomic, and metabolomic approach to investigate the molecular mechanisms underlying the plant’s resistance to A. alternata, of which little is known. We found that A. alternata infection stimulated the outbreak of reactive oxygen species (ROS) in cherry. The responses of the antioxidant enzymes and chitinase to disease were observed earlier in the RC than in the SC. Moreover, cell wall defense ability was stronger in the RC. Differential genes and metabolites involved in defense responses and secondary metabolism were primarily enriched in the biosynthesis of phenylpropanoids, tropane, piperidine and pyridine alkaloids, flavonoids, amino acids, and α-linolenic acid. Reprogramming the phenylpropanoid pathway and the α-linolenic acid metabolic pathway led to lignin accumulation and early induction of jasmonic acid signaling, respectively, in the RC, which consequently enhanced antifungal and ROS scavenging activity. The RC contained a high level of coumarin, and in vitro tests showed that coumarin significantly inhibited A. alternata growth and development and had antifungal effect on cherry leaves. In addition, differentially expressed genes encoding transcription factors from the MYB, NAC, WRKY, ERF, and bHLH families were highly expressed, they could be the key responsive factor in the response of cherry to infection by A. alternata. Overall, this study provides molecular clues and a multifaceted understanding of the specific response of cherry to A. alternata.